Evolution of electromyographic signal, running economy, and perceived exertion during different prolonged exercises - Hausswirth, C.; Brisswalter, J.; Vallier, J. M.; Smith, D.; Lepers, R. (International Journal of Sports Medicine, 2000)
The purpose of this study was to compare the electromyographic (EMG) signal of the vastus lateralis muscle obtained during a run section of a triathlon and at the end of a prolonged run performed at the same running velocity. Seven subjects were studied on three occasions: a 2 h 15 min triathlon (30 min swimming, 60 min cycling, and 45 min treadmill running at 75% of the maximal aerobic speed), a 2 h 15 min run, where the last 45 min (Prolonged Run, PR) were run at the same speed as the Triathlon Run (TR) on a motorized treadmill, and a 45 min Isolated Run (IR) performed at the same TR and PR velocity. The three experimental trials were randomised. Oxygen uptake (VO2), heart rate (HR), and EMG data were recorded during the three run sections. The results confirm a greater VO2 and HR during PR compared with IR (P<0.01) and TR (P<0.05). Also the VO2 values obtained during TR were significantly greater compared to IR (P < 0.05). EMG signal, obtained from the vastus lateralis muscle during 4 sec of isometric contraction at 35 % of maximal voluntary contraction (MVC), showed that after PR the mean power frequency (MPF) shifted significantly to lower frequencies (P<0.01) compared with MPF recorded before the prolonged run. Moreover, the signal amplitude (RMS) was increased significantly after PR in comparison to pre-trial (P < 0.01). Similar results were obtained for the TR at P < 0.05. The integrated EMG flow, QIEMG (iEMG/burst duration), recorded during all run sections, was significantly increased near the end of PR (i.e. 2 h 10 min of running) compared with QiEMG recorded after 1 h 30 min of running. No significant increase in QiEMG was observed with TR and IR situations. The results suggest that a long exercise bout of running led to a greater increase in muscle fatigue compared with a triathlon or an isolated run performed at the same running speed. In addition it is suggested that the rating of perceived exertion recorded during isometric contractions is a good indice to approach the level of fatigue during prolonged exercises.